Studi tentang Fenomena Ebeg Anak-Anak di Kelompok Trenggini Kento Sukmo Bobosan Purwokerto Utara - chusmeru chusmeru (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2011)
Involvement of children in the ebeg arts in the group Trenggini Kento Sukmo invite trouble. Thestudy aimed to verify the process of becoming a player ebeg, reasons and motives. Informantswere selected purposively to members ebeg art. The results showed, they become players througha process of ritual ebeg Indang search. Their motivation is the love and preservation of local culture.Most parents fearing they do not support interrupt the learning process. Their achievementsin school are unsatisfactory.